(untitled) - Goddard, Elizabeth (Thorndike, Maine, 2024)
"Montana Detective Trevor West is desperate to learn what happened to his sister, who went missing in Alaska over a year ago, leaving nothing but a few photographs as clues to her whereabouts. At the advice of Police Chief Autumn Long, Trevor enlists the help of an experienced bush pilot. If Carrie James cant help him find the places in the photographs, no one can. But Carrie has her own agenda. Grieving the death of her closest friend and the only person she could trust, Carrie will help Trevor find his sister on one condition -- that he help her track down her friends killer. As the two close in on the answers they crave, theyll face dangers and connections they could not have imagined. Theyll have to learn to trust one another -- and face the dark secrets of the past -- if they are ever to discover the truth and bring a killer to justice."--
Keywords: Fiction; Man-woman relationships; Bush pilots; Fiction; Investigation; Murder; Fiction; Missing persons; Fiction; Alaska; Fiction; Large print books; Christian fiction; Thrillers (Fiction); Detective and mystery fiction